Association between post-orthodontic treatment gingival margin alterations and symphysis dimensions - Closs, Luciane Q.; Bortolini, Leonardo F.; dos Santos-Pinto, Ary; Rösing, Cassiano K. (My University, 2014)
Orthodontic therapy is known to be associated with the development of gingival recession. Several factors may be involved in the causal chain of this outcome, including anatomical and behavioral aspects. Among the anatomical aspects, the dimensions of the mandibular symphysis could play a predisposing role. This study evaluated the relationship between the mandibular symphysis dimensions prior to orthodontic therapy and the development of gingival recessions on the lower incisors and cuspids. Records from 189 orthodontically treated adolescents were evaluated, including radiographs, casts and intra-oral photographs. Symphysis dimensions were assessed by cephalograms. Gingival margin alterations were determined in photographs and cast models. Association between gingival margin alterations and symphysis dimensions was tested by chi-square (α=0.05). Occurrence of gingival recession increased after orthodontic therapy. No association was observed on average of symphysis dimensions and the occurrence of gingival recessions. It may be concluded that pretreatment symphysis dimensions may not be used as predictors of gingival recession after orthodontic therapy.